Park(ing) Day : label international d’un activisme édulcoré? - Douay, Nicolas; Prevot, Maryvonne (Environnement urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2014)
The movement of Park(ing) Day proposes to transform for a day a parking spot into a green, artistic, recreational and citizen space. Created in 2005 by the group REBAR in San Francisco the event is now an annual and international appointment, which relies on a wide network of local activists. From case studies in Paris, Lille, Brussels and Montreal, this article examines the global process of labeling of this movement and also questions the implications of the labeling on the activist practices. The institutionalization of Park(ing) Day illustrates a contemporary form of “sweetened” activism, which means less conflict.